Pengaruh Kualitas Pelayanan, Kualitas Produk, Dan Harga Terhadap Kepuasan Pelanggan Fans.Net Di Desa Watukebo Banyuwangi - Imamuddin Irfani; Muhammad Ridwan Basalamah; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This research sets out to examine the role of three variables—service quality, product quality, and price—in shaping customer satisfaction, looked at both simultaneously and partially. The subjects of the study are subscribers of Fans.net residing in Watukebo Village, Banyuwangi, whose total number could not be determined precisely. Sampling was carried out through a non-probability route, specifically purposive sampling, which selects respondents on the basis of predetermined criteria. A questionnaire was administered to 90 participants, and the responses were processed using SPSS. Findings demonstrate that the three predictors, taken together, exert a significant influence on customer satisfaction. When tested individually, however, only service quality and product quality registered statistically significant effects, whereas price did not. Keywords: Service Quality, Product Quality, Price, Customer Satisfaction.